Pemberdayaan Perempuan melalui Inovasi Pengolahan Sari Kedelai untuk Ketahanan Pangan dan Kemandirian Ekonomi Keluarga - Rahayu Widowati; Sri Sari Utami (Jurnal Atma Inovasia, 2026)
Empowering housewives through the strengthening of local resource–based food processing skills is a strategic approach to enhancing food security while simultaneously promoting household economic self-reliance. This community service program aimed to enhance the knowledge capacity, technical skills, and entrepreneurial orientation of housewives through innovation in soybean processing into soy milk with various flavour. The program involved 35 housewives residing in Jolosutro, Srimulyo Village, Bantul Regency, and was implemented using a Participatory Rural Appraisal (PRA) approach. The implementation methods included participatory discussions, extension activities, hands-on processing training, and assistance in the development of home-based enterprises. The results indicate an improvement in participants’ understanding of the nutritional value of soybeans and the importance of food diversification, as well as enhanced technical skills in the hygienic production of soy milk. Furthermore, product innovation emerged through the development of various flavour, accompanied by increased interest among participants in developing soy milk as a home-based enterprise. Overall, this community service activity contributes significantly to strengthening community capacity through the sustainable utilization of local resources.